Ṭarīqat al-Miftāh li al-‘Ulūm fī Tarqiyyat Mahārat al-Qirā’ah - Ahmad Tibbil Qulub; Nuril Mufidah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2019)
Studying in religious institutions is inseparable from the kitab turats, so the ability to read it well is a must for students. This study aims to describe the process of applying the Miftahul Ulum method in Ma'had An-Nur 2 Al-Murtadho and supporting factors in the learning process using the method. This research was conducted with a qualitative descriptive approach. Observation, interviews, and documentation collected data. The results of this study indicate that the application of the Miftahul Ulum method can improve the ability to read the yellow book. The indicators are: increase in score and learning the ability. This can be seen from teaching and learning activities; students can distinguish the position of the sentence and be able to read the kitab turats well.